LA INSCRIPCIÓN DEL NACIDO VIVO EN FORMA CONJUNTA POR LOS CÓNYUGES PARA GARANTIZAR EL DERECHO A SU IDENTIDAD” - Salinas Ochoa, Andrés David (2020)
Identity is an intrinsic right of the person, because from it, the human being acquires rights and obligations that will accompany him for the rest of his life, then, given the importance of the same, shouldn't the State owe it for all possible means at your fingertips look for ways to protect and safeguard this right? In this thesis work, it is intended to demonstrate how transcendent it is for the human being to have a real identity that allows him to hold all those rights inherent to his person, and that are subject until the moment of registration in the entities of the Civil registration. But this is not merely a formal act, identity is the very essence of the person, their beliefs, their culture, their origin, and of course the family trunk from which it comes, which becomes the main axis of their individuality. In every marriage the principle of fidelity is present, which constitutes the creation of both emotional and carnal ties only with your partner, more, it happens that when this principle of “sexual exclusivity” is lacking, and a third person enters into the marriage, we are exposed to the fact that as naturally occurs in a marriage, the conception can be given in women, and that in this case it is the minor, the directly affected, because the Law presumes that because its parent is within a nexus Spousal, the fruit of his womb has the same husband's father, thus depriving the child of accessing the right to his real identity, and knowing and receiving care, love and protection from his true parents. That is why in the development of the thesis it will be demonstrated the importance that, despite the marriage situation, it is both parents who come to register the birth of the child in the Civil Registry, in an act of will, without defects of no class that can be triggered in the future in legal problems, due to the genetic incompatibility of the mother's spouse with respect to her alleged child.